Genre fission : a new discourse practice for cultural studies - Barr, Marleen S. (University of Iowa Press, 2000)
What do Amsterdam prostitutes, NASA astronauts, cross-dressing texts, and Star Trek characters have in common? In Genre Fission, Marleen Barr wittily and eccentrically revitalizes cultural and literary theory by examining the points where such vastly different categories meet, converge, and reemerge as something new.
Keywords: American fiction -- 20th century -- History and criticism -- Theory, etc.; Postmodernism (Literature) -- United States.; United States -- Civilization -- 20th century.; Postmodernism -- United States.; Discourse analysis, Literary.; Culture -- Philosophy.; Literary form.; Roman américain -- 20e siècle -- Histoire et critique -- Théorie, etc.; Postmodernisme (Littérature) -- États-Unis.; Postmodernisme -- États-Unis.; Discours littéraire.; Culture -- Philosophie.; Genres littéraires.; États-Unis -- Civilisation -- 20e siècle.; literary criticism.; LITERARY COLLECTIONS -- Essays.; LITERARY CRITICISM -- Semiotics & Theory.; American fiction; Civilization; Culture -- Philosophy; Discourse analysis, Literary; Literary form; Postmodernism; Postmodernism (Literature); United States; 1900-1999; Criticism, interpretation, etc.